The Effect of Katuk Leaf Soup (Sauropus Androgynus) on the Amount of Breast Milk of Postpartum Mothers at PMB Ade Mila Marliana, Babakan Jawa, Majalengka in 2023 - Annisa Zain, Dhiya; Mutya Sari, Vianty; Tonasih, Tonasih (Ann Publisher, 2024)
Breast milk is the best liquid for newborns until the age of 6 months, because the components of breast milk are easily digested and absorbed by the baby's body. There are many ways to increase breast milk, one of them is by consuming traditional medicinal plants, namely katuk leaf. The purpose of this research is to determine the effect of katuk leaf soup on the amount of breast milk for postpartum mothers at PMB Ade Mila Marliana, SST. This research used pre-experimental design with one-group pre-post test design. The population in this research was all postpartum mothers who gave birth at PMB Ade Mila Marliana, S.ST for the period April-May 2023 as many as 20 people. Sampling in this research using total sampling technique. Data analysis includes univariate analysis using frequency distribution and bivariate analysis using the Wilcoxon test. The results of the analysis using Wilcoxon obtained a p value of 0.000 (<0.05). The conclusion of this research is that there is an effect of katuk leaf (Sauropus Androgynus) on the amount of breast milk for postpartum mothers at PMB Ade Mila Marliana, SST Kelurahan Babakan Jawa, Kabupaten Majalengka. This research is expected to be an input for further researchers to develop research related to the effect of katuk leaf on the amount of breast milk for postpartum mothers.